Environmental factors related to the incidence of personality disorders in students of the nursing faculty of the national university Hermilio Valdizán - Huánuco 2014 - Villavicencio Guardia, Maria (2017)
To determine the environmental factors related to the incidence of personality disorders in studentsof the Faculty of Nursing.The sample consisted of 17 students the first year, 16 students of the second, 16 third graders,15 fourth year students and 15 students of the fifth year. A descriptive study transverse no such program (because only such phenomena is observed and as given in its natural context). Data werecollected at one time, in one time. Data related to the presence or absence of personality disordersin the student consists of 119 questions total of 238 (119 items, each affirmative answer 1 point, andthe refusal 0 zero) According to the statistical process data will be processed through SPSS version21, of which the data is taken into account in the statistical tables according to the objectives andvariables under study.A total of 79 students of the faculty of nursing freshmen in the fifth year of which 21 studentshave studied Personality Disorder Avoidant 10 dependent personality disorder, obsessive compulsivedisorder 27 personality disorder 14 passive aggressive personality, May depressive personality disorder,paranoid personality disorder 12 5 schizotypal personality disorder type, 21 schizoid personalitydisorder type, 4 histrionic personality disorder type, 13 narcissistic personality disorder type, 10show personality disorder borderline type. And the environmental factors related to personalitydisorders were the humiliation (70) students, followed child abuse (39) and emotional trauma (28)According to the study the incidence of personality disorders is observed that the three most commondisorders identified in students of nursing faculty are respectively; obsessive compulsive disorderspersonality, which is the highest proportion, followed by avoidant personality disorders, and passiveaggressive personality disorder and major environmental factor related to personality disorder wasthe humiliation.